Implementasi Model Pembelajaran Project Based Learning (PjBL) pada Teks Hikayat dan Cerpen dengan Proyek Video di Kelas X SMA Negeri 1 Kota Mojokerto - Iliya Ulva; Uut Istianah; Nada Vanca Anggrestia; Sefira Amelia Rosadha; Tannia Alfianti Putri; Wiwik Mardiana; Hilda Purnamasari (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The application of an appropriate learning model to a particular material will make it a successful achievement. The purpose of this research is to explore and describe the implementation of the Project-Based Learning (PjBL) model in teaching the material of hikayat texts and short stories through video projects in class X at SMA Negeri 1 Kota Mojokerto. This study uses both primary and secondary data sources. The primary data was obtained from student participation in the implementation of the Project-Based Learning (PjBL) model, while the secondary data includes various relevant literatures, journals, and previous studies. Based on observations, the implementation of the Project-Based Learning (PjBL) model in class X at SMA Negeri 1 Kota Mojokerto has shown positive results and supports the development of students' skills in understanding the material. The use of video projects as part of PjBL has successfully attracted students' interest, encouraging them to be more active and creative in learning about Hikayat texts and short stories. Overall, the implementation of the PjBL learning model in the teaching of Hikayat texts and short stories at SMA Negeri 1 Kota Mojokerto has proven successful in improving the quality of learning and students' skills.